Transforming Creative Ideas into Productive MSMEs: An Analysis of Studentpreneurship in Stafi Bouquet - Safiratunnisa’ Ansari Putri; Mashudi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study aims to analyze the process of transforming creative ideas into productive micro, small, and medium enterprises (MSMEs) within the context of studentpreneurship. This study uses a case study of the Stafi Bouquet business owned by Mustafida, a student who started her business before college. This study used a descriptive qualitative approach, collecting data through in-depth interviews. The results indicate that the success of the Stafi Bouquet business stems not only from personal interests and experiences, but also from the owner's ability to manage time, utilize social media as a promotional tool, and understand market needs through flexible and varied product offerings. Furthermore, the learning process during college and extensive campus connections are also important factors in business development. This study emphasizes the importance of supporting studentpreneurship as a concrete effort to encourage the growth of MSMEs among students. The implications of these findings are expected to contribute to educational institutions and policymakers in designing strategies for empowering young entrepreneurs in Indonesia.